Developing a tongue shape index for traditional Chinese medicine - Png, Ming Jian (Nanyang Technological University, 2021)
Tongue diagnosis is a fundamental and indispensable diagnosis method in Traditional Chinese Medicine (TCM). The human tongue is believed to be linked to different organs of the human body and thought to reflect one’s health. TCM practitioners perform tongue diagnosis to access their patient’s health. The key features that practitioners pay attention to includes the tongue colour, the thickness of the tongue coating and the tongue’s shape. A key issue faced by TCM tongue diagnosis is its subjective nature. The process of tongue diagnosis is closely linked with the TCM practitioners experience and judgement. As a result, inconsistencies would arise, such as the same patient receiving different diagnosis from different TCM practitioners. The lack of a systematic and quantifiable approach to tongue diagnosis also contributed to the inconsistency of this method. Research has been done in this area hoping to quantify and benchmark certain metrics to in tongue diagnosis and create a standardised approach. There are currently several approaches taken by researchers around the world to establish tongue imaging systems that carry out tongue diagnosis. However, these systems often require a complex set-up, and are potentially costly to adopt. In this Final Year Project (FYP), the author will be focused on establishing a consistent Tongue Shape Index, a scientific approach to differentiate between the eight different tongue shapes. The eight tongue shapes are categorised as obtuse triangle, obtuse triangle-circle, circle, circle-square, square, acute triangle, ellipse4 and rectangle shape. Two methodologies will be proposed and tested to determine which approach is adopted in the Tongue Shape Index. The author will also test and implement a wireless transmission system for the NTU Tongue Imaging System. This system will allow TCM practitioners to transmit and receive their patients’ tongue information remotely using smartphones and replace the need for a wired connection and a personal computer set-up. This project is a continuation of previous FYP’s efforts, which involves research on creating a colour correction technique, a Tongue Colour Index, a Tongue Coating Thickness Index and using a smartphone as a mobile tongue imaging system. The objective of this FYP is to build on this existing body of work by creating a quantifiable Tongue Shape Index and creating a wireless data transmission system for the tongue imaging system.